Teacher collaborative agency: preliminary results of an empirical study on group work in project design activities - Chiara Urbani (Firenze University Press, 2024)
Several studies refer to the importance of effective collaborative practices in the teachers' working groups both for the development of learning organisations and in the creation of life project for self-training and personal fulfilment. The study on the constructs of collaborative agency and shared epistemic agency identifies the framework of the research, carried on two teacher-students' groups within the specialization course for special needs teacher at the University of Trieste (TFA). The aim is to explore and describe the characteristics of teachers' group collaborative agency in dealing with an instructional design task, through a textual and thematic analysis of the verbal interactions identified by the case studies on group's actions. Preliminary findings suggest some critical issues in the group's epistemic agency related to the systematic actions developed to effectively deal with the task.   Agency collaborativa docente: primi risultati di un'indagine empirica su lavori di gruppo in compiti progettuali autentici. Diversi studi dimostrano l'importanza di pratiche collaborative efficaci nel team docente sia per lo sviluppo di learning organisation che entro la costruzione di progettualità personali in senso formativo e realizzativo. Lo studio dei costrutti dell'agency epistemica e collaborativa condivisa definisce il quadro della ricerca condotta su due gruppi di studenti-docenti nell'ambito del percorso di specializzazione sul sostegno dell'Università degli Studi di Trieste (TFA). L'obiettivo è quello di esplorare e descrivere le caratteristiche dell'agency collaborativa di gruppo dei docenti nell'affrontare un compito di progettazione didattica, attraverso l'analisi testuale e tematica delle interazioni verbali rilevate con lo studio di caso sulle azioni di gruppo. I risultati segnalano criticità nell'agency epistemica di gruppo riferita alle azioni sistematiche prodotte per affrontare efficacemente il compito.